Raising Awareness in Five Poems by Kamala Das - Chairunnisa Maulana Fitrah; An Fauziah Rozani Syafei (Universitas Negeri Padang, 2019)
This article is about the analysis of the five poems by Kamala Das entitled An Introduction, The Looking Glass, The Sunshine Cat, The Old Playhouse and The Suicide, these poems are analyzed by combining the elements of poetry; symbol, irony, and repetition which contribute to revealing the raising awareness. The analysis is based on the concept of Feminist Literary approach by Julia Kristeva and The concept of Self-awareness from Crisp & Turner.